Lattice changes in shape memory CuZnAl alloys on aging at room temperature - Çakmak, Seyfettin; Artunç, Ekrem; Kayali, Nejdet; Adigüzel, Osman (My University, 2001)
The aging behavior of CuZnAl martensites (Cu-21.62 wt.% Zn-5.68 wt.% Al and Cu-24.98 wt.% Zn-4.43 wt.% Al) at about 297 K was studied by analyzing diffraction line profiles obtained by X-ray diffractometry. For the alloys, the change of the lattice parameters and the tetragonality associated with the aging time at room temperature were investigated. The habit planes versus the aging time at room temperature were calculated using the De Vos-Aernoundt-Delaey model, based on the crystallographic theory of Wechsler-Lieberman-Read(WLR), and from the DO3?18R martensite transformation theory.